A ARABIC-AL-ZARKASHI'S APPROACH IN HIS STUDY OF THE RHETORICAL MIRACLE IN THE HOLY QUR'AN - Abdul Majeed Baghdadi; Shabana Nazar (دی اسکالر)
Al-Zarkashi is of Turkish origin, Egyptian, by birth and death, as he was born in Cairo in the year 745 AH, when it was inhabited by schools, full of virtues and knowledge bearers, full of private and public books, and mosques filled with students of science and knowledge, and those who came from something else, but his father was from the Turks and was owned by some of the most prominent. The Book of Al-Burhaan in the Sciences of the Qur’an is one of the many books that collected the essence of the sayings of the forerunners, and the elite opinions of the investigators about the Noble Qur’an (and if Badr al-Din al-Zarkashi had no one else, it would have sufficed him). Students and scholars, until Jalal al-Din al-Suyuti came and wrote his book (Al-Itqan fi Ulum al-Qur’an). Although the book is relatively late, it is considered one of the mothers of books in the sciences of the Qur’an that a researcher in this field. Whoever reviews this book will find it rightly a great encyclopedia in the sciences of the Qur’an, as its author has collected forty-seven types of subjects of the Qur’anic sciences and collected various private and public issues in each branch, including the sayings of scholars, commentators, jurists, and fundamentals, and other issues of speakers and companions. The controversy, and the issues of Arabic, came as described by its author.